THE PEDAGOGICAL COMPETENCE OF CIVIC TEACHERS IN SMA KORPRI BANJARMASIN - Isrianti, Muzada (Jurnal Pendidikan Kewarganegaraan, 2014)
Muzada Isrianti. 2013. The Pedagogical Competence of Civic Teachers in SMA KORPRI Banjarmasin.Sarjanaâs Thesis. Civic Education Department, Faculty of Teacher Training and Education,Lambung Mangkurat University Banjarmasin. The first advisor (I) Acep Supriadi, the second advisor(II) Harpani MatnuhÂ Pedagogical competence is a basic competence for the teachers in implementing teaching process. In fact, the teachers do not fully apply pedagogical competence in teaching and learning process yet. Therefore, this research was purposed to find out the quality of pedagogical competence of civic teachers, and efforts that the teachers done to increase their pedagogical competence.The research method used was qualitative method through observation, interviews, and documentation. The data sources were taken by the result of interviews with the key informants and documentation to the research objects. Then they were analyzed through data reduction, data presentation, and taking conclusion.The result of this research showed that the civic teachers in SMA KORPRI Banjarmasin had good pedagogical competence in teaching. The teachers understood their studentsâ characteristics, mastered learning theory and educated principal teaching and learning. They were also able to develop curriculum of civic subject, to make teaching instructional media, to conduct assessment and evaluation of teaching, and to use the result of assessment as the input for the next teaching process. However, there were some pedagogical competences that were not maximally implemented yet. Some obstacles during the implementation of pedagogical competence were the lack of teachersâ motivation in increasing the competence, the lack of teaching and learning facilities, the lack of mastering information and technology (IT) and the studentsâ condition. Several efforts done by the teachers to improve their pedagogical competence were following diklat (education and training) and other kinds of activities and training.Based on the results above, it can be suggested to the teachers, especially to teachers of SMA KORPRI Banjarmasin, to fully apply their pedagogical competence in conducting teaching and learning process and always to try improving their knowledge and skills to develop their pedagogical competence.Â Keywords: Pedagogical Competence, Teacher, Civic education